Steel Sheets and Enameled Products

A steel sheet with a tailored chemical composition addresses the challenges of achieving high strength and excellent enamel properties by optimizing solid solution strengthening and pickling processes, resulting in improved tensile strength and enamel performance for enamel products.

JP7648978B2Active Publication Date: 2025-03-19NIPPON STEEL CORPORATION
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024514803
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-04-11
Filing Date
2022-12-26
Publication Date
2025-03-19
Estimated Expiration
2042-12-26

AI Technical Summary

Technical Problem

Existing enamel products and steel sheets face challenges in achieving high strength and excellent enamel properties such as claw skipping resistance, adhesion, and appearance after enamel treatment, while also experiencing issues like surface defects and reduced adhesion due to hydrogen penetration and pickling processes.

Method used

The development of a steel sheet with a specific chemical composition, including controlled amounts of P, Sn, Sb, and other elements, which enhances tensile strength and enamel properties by optimizing solid solution strengthening and pickling processes.

Benefits of technology

The resulting steel sheet achieves higher tensile strength and excellent enamel properties, including improved claw skipping resistance, adhesion, and appearance, making it suitable for use in kitchenware, building materials, and energy fields, while also contributing to weight reduction in enamel products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648978000006
    Figure 0007648978000006
  • Figure 0007648978000001
    Figure 0007648978000001
  • Figure 0007648978000002
    Figure 0007648978000002
Patent Text Reader

Abstract

This steel sheet has a chemical composition containing, in terms of mass%, at most 0.0050% of C, at most 0.050% of Si, 0.007-1.00% of Mn, 0.020-0.200% of P, 0.005-0.050% of S, at most 0.010% of Al, 0.0100-0.1000% of O, 0.010-0.060% of Cu, at most 0.0050% of N, 0.010-1.00% of Cr, a total of at least 0.11% of one or two of 0.010-1.00% of Sn and 0.010-1.00% of Sb, and a total of 0-0.100% of at least one selected from the group consisting of B, Ni, Nb, As, Ti, Mo, Se, Ta, W, La, Ce, Ca, and Mg, with the remainder consisting of Fe and impurities, wherein when the Sn content is defined as [Sn], the Sb content is defined as [Sb], and the P content is defined as [P], in terms of mass%, expression (1) is satisfied, and the tensile strength obtained in a tensile test carried out in accordance with JIS Z 2241:2011 is at least 340 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to steel sheets and enamel products. This application claims priority based on Japanese Patent Application No. 2022-064917, filed on April 11, 2022, the contents of which are incorporated herein by reference. [Background technology]

[0002] Enameled products are made by baking a glassy substance onto the surface of a steel sheet. Enameled products have the functions of heat resistance, weather resistance, chemical resistance, and water resistance, and therefore have been widely used in the past as materials for kitchen utensils such as pots and sinks, as well as building materials. Such enamel products are generally manufactured by processing steel sheets into a predetermined shape, assembling them into the product shape by welding or the like, and then carrying out an enameling process (firing process).

[0003] Steel sheets used as materials for enamel products (steel sheets for enamel) are required to have properties such as resistance to firing distortion, resistance to nail chips after enamel treatment, adhesion to enamel, and resistance to bubbles and black spot defects after enamel treatment. Nail popping is a phenomenon in which the enamel layer is damaged within about one week after firing, causing crescent-shaped pieces to peel off. It is thought that the reason for this is that hydrogen that penetrates and dissolves in the steel sheet during the enamel firing process turns into gas after cooling and collects at the interface between the steel sheet and the glaze, causing the enamel layer to break down due to the pressure of the hydrogen gas. In addition, in some applications of enamel products, there is a demand for higher strength steel sheets to reduce the weight of parts, because weight reduction reduces the burden on workers and the number of workers required, which leads to cost reduction.

[0004] Regarding increasing the strength of enamel products, for example, Patent Document 1 discloses a technology for increasing strength by adding Ti to steel and finely precipitating TiC in the steel sheet during enamel firing (the firing step in the enamel treatment). Patent Document 2 discloses a technology for optimizing the contents of C, Mn, P, and Nb to reduce the crystal grain size before and after enamel firing, thereby increasing strength and fatigue strength.

[0005] However, in the technology of Patent Document 1, when the steel sheet is subjected to an enamel treatment, surface defects called bubbles or black spots are likely to occur. Also, in the short heat treatment during firing, TiC is difficult to generate sufficiently, and nail chip defects are likely to occur. Furthermore, the technology of Patent Document 2 is based on dry enamel that does not undergo pretreatment such as pickling or Ni treatment. With wet enamel, which requires pretreatment, the enamel adhesion decreases and nail chip defects are likely to occur. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Publication No. 61-117246 [Patent Document 2] Japanese Patent Publication No. 58-31063 Summary of the Invention [Problem to be solved by the invention]

[0007] As described above, there has been no disclosure up to now of an enamel product having high strength and excellent enamel properties (resistance to chipping, adhesion, appearance) and a steel sheet for enamel that is the material for such an enamel product. Therefore, an object of the present invention is to provide a steel sheet that can provide high strength and excellent enamel properties (nail resistance, adhesion, appearance) after enameling treatment. Another object of the present invention is to provide an enamel product that includes the above steel sheet and has excellent enamel properties. [Means for solving the problem]

[0008] The present invention was developed to improve the tensile strength of enameled steel sheets while providing the same or better enamel properties (resistance to chipping, adhesion (enamel adhesion), and appearance after enameling) as conventional enameled steel sheets. As a result, the following findings were obtained regarding the effects of chemical composition and manufacturing conditions. 1) Solid solution strengthening by P is effective in improving the strength of steel sheets. 2) On the other hand, when P is added, the pickling loss increases significantly, and the steel sheet surface becomes covered with smut during the pickling process before enamel treatment, which reduces the adhesion and nail chip resistance after enamel treatment. 3) On the other hand, Sn and Sb adhere to the surface of the steel sheet during the pickling process and have the effect of delaying the dissolution of the surface of the steel sheet. 4) Therefore, by controlling the Sn content and / or Sb content to a predetermined range relative to the P content, it is possible to obtain the effect of solid solution strengthening by P while suppressing an increase in pickling loss.

[0009] The present invention has been made based on the above findings. The gist of the present invention is as follows. [1] A steel sheet according to one embodiment of the present invention has, by mass%, C: 0.0050% or less, Si: 0.050% or less, Mn: 0.007 to 1.00%, P: 0.020 to 0.200%, S: 0.005 to 0.050%, Al: 0.010% or less, O: 0.0100 to 0.1000%, Cu: 0.010 to 0.060%, N: 0.0050% or less, Cr: 0.010 to 1.00%, Sn: 0.010 to 1.00%, and Sb. The alloy has a chemical composition consisting of one or two of 0.010-1.00% in total of 0.11% or more, one or more selected from the group consisting of B, Ni, Nb, As, Ti, Mo, Se, Ta, W, La, Ce, Ca, and Mg in total of 0-0.100%, and the balance: Fe and impurities, and satisfies the following formula (1) when the Sn content is [Sn], the Sb content is [Sb], and the P content is [P], in mass%, and has a tensile strength of 340 MPa or more as obtained by a tensile test performed in accordance with JIS Z2241:2011. 2.0≦([Sn]+[Sb]) / [P]≦11.5 (1) [2] In the steel sheet according to the above [1], the [Sn], the [Sb], and the [P] may satisfy the following formula (2): 2.3≦([Sn]+[Sb]) / [P]≦11.0 (2) [3] The steel plate according to the above item [1] may have a yield stress or 0.2% proof stress, as determined by the tensile test, of 240 MPa or more. [4] The steel plate according to the above item [2] may have a yield stress or 0.2% proof stress, as determined by the tensile test, of 240 MPa or more. [5] The steel sheet according to any one of the above [1] to [4] may be a cold-rolled steel sheet. [6] The steel sheet according to any one of the above [1] to [4] may be a steel sheet for enamel. [7] The steel sheet in [5] above may be a steel sheet for enamel. [8] The enamel product according to another embodiment of the present invention has the chemical composition described in [1] or [2] above. The steel plate has a tensile strength of 310 MPa or more in a tensile test conducted in accordance with JIS Z2241:2011. do. Effect of the Invention

[0010] According to the above-mentioned aspect of the present invention, it is possible to provide a steel sheet that can obtain high strength and excellent enamel properties (nail chipping resistance, adhesion, appearance) after enameling. The tensile strength of this steel sheet after enameling is higher than that of conventional steel sheets for enameling. Therefore, it is suitable as a steel sheet for enameling, which is a base material for enamel products applied in the fields of kitchen utensils, building materials, energy, etc., and contributes to weight reduction of the products. Furthermore, the present invention can provide an enamel product having high strength and excellent enamel properties, which is suitable for use in kitchen utensils, building materials, the energy field, and the like. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a graph showing the relationship between adhesion and ([Sn]+[Sb]) / [P]. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] A steel sheet according to one embodiment of the present invention (the steel sheet according to this embodiment) and an enamel product according to one embodiment of the present invention (the enamel product according to this embodiment) will be described.

[0013] [Steel plate] The steel sheet according to this embodiment has a predetermined chemical composition described later, and satisfies 2.0≦([Sn]+[Sb]) / [P]≦11.5, where [Sn] is the Sn content, [Sb] is the Sb content, and [P] is the P content, all in mass%, and has a tensile strength of 340 MPa or more in a tensile test performed in accordance with JIS Z2241:2011.

[0014] <Chemical composition> The chemical composition (chemical components) of the steel sheet according to this embodiment will be described below. The percentages relating to the contents of each element are mass percent unless otherwise specified.

[0015] C: 0.0050% or less If the C content exceeds 0.0050%, bubble defects tend to occur in the enamel and press workability also deteriorates. Therefore, in terms of product performance, the lower the C content, the better. However, excessive reduction of C requires a long processing time at the steelmaking stage, and steelmaking costs also increase. Therefore, taking into consideration the balance between cost and properties, the C content is set to 0.0050% or less. The C content is preferably 0.0040% or less, more preferably 0.0030% or less, and even more preferably 0.0020% or less. In terms of product performance, the lower the C content, the better. However, taking into consideration the steelmaking costs, the C content may be set to 0.0010% or more.

[0016] Si:0.050% or less Silicon is a deoxidizing element. If the silicon content exceeds 0.050% and becomes excessive, it becomes difficult to control the oxides that are effective in improving the nail chip resistance. Therefore, the silicon content is set to 0.050% or less. From the viewpoint of improving bubble resistance, black spot resistance, etc., and obtaining better surface properties after enamel treatment, the silicon content is preferably set to 0.008% or less. The Si content may be 0%, but an excessive reduction in the Si content will increase costs, so the Si content may be 0.001% or more.

[0017] Mn: 0.007 to 1.00% Mn is an element that generates oxygen-containing inclusions and contributes to improving enamel properties, and also has the effect of preventing hot embrittlement caused by S. To obtain this effect, the Mn content is set to 0.007% or more. The Mn content is preferably 0.010% or more, and more preferably 0.10% or more. On the other hand, Mn is an element that has the effect of lowering the transformation point of steel. If the Mn content is excessive, transformation occurs within the firing temperature range. In addition, the workability of the steel also decreases. For these reasons, the Mn content is set to 1.00% or less. The Mn content is preferably 0.50% or less.

[0018] P: 0.020~0.200% P is an element that has the effect of increasing the strength of a steel sheet by solid solution strengthening. If the P content is less than 0.020%, the strength improvement effect by solid solution strengthening is small. Therefore, the P content is set to 0.020% or more. The P content is preferably 0.050% or more. On the other hand, P is an element that increases the pickling weight loss of the steel sheet during pickling in the enamel pretreatment. It is also an element that significantly reduces the deformability of the steel sheet. Therefore, if the P content exceeds 0.200%, these adverse effects become significant, so the P content is set to 0.200% or less. The P content is preferably 0.0150% or less.

[0019] S: 0.005~0.050% S is an element that has the effect of increasing the pickling speed, roughening the surface of the steel sheet after pickling, and improving the adhesion of enamel. To obtain this effect, the S content is set to 0.005% or more. The S content is preferably 0.010% or more. On the other hand, if the S content is excessive, the effect of Mn necessary for controlling oxides in the steel may decrease, so the S content is set to 0.050% or less.

[0020] Al: 0.010% or less Al is a strong deoxidizing element. If the Al content exceeds 0.010%, it becomes difficult to retain the required amount of O (oxygen) in the steel, and it becomes difficult to control the oxides that are effective in improving the resistance to chipping. Therefore, the Al content is set to 0.010% or less. The Al content is preferably 0.005% or less. There is no need to set a lower limit for the Al content, but from the viewpoint of controlling the oxygen content, the Al content may be 0.001% or more.

[0021] O: 0.0100~0.1000% O is a constituent element of fine inclusions that capture hydrogen in steel and improve nail chip resistance, and is an important element in enameled steel sheets. In the steel sheet according to this embodiment, the O content is set to 0.0100% or more in order to ensure the desired enamel properties. If the O content is less than 0.0100%, the inclusions are not sufficiently formed and the nail chip resistance is reduced. The O content is preferably 0.0120% or more, more preferably 0.0150% or more, and even more preferably 0.0200% or more. On the other hand, if the O content is excessively high, the ductility of the steel sheet deteriorates. Therefore, the O content is set to 0.1000% or less, and preferably 0.0800% or less.

[0022] Cu: 0.010~0.060% Cu is an element that reduces pickling weight loss and forms fine irregularities on the surface of the steel sheet after pickling, improving adhesion (enamel adhesion). If the Cu content is less than 0.010%, the effect of improving adhesion is insufficient. Therefore, the Cu content is set to 0.010% or more. The Cu content is preferably 0.015% or more, and more preferably 0.020% or more. On the other hand, if the Cu content exceeds 0.060%, the dissolution rate of the steel is too low, and the above-mentioned unevenness is not formed sufficiently. In this case, good enamel adhesion cannot be obtained. Therefore, the Cu content is set to 0.060% or less. The Cu content is preferably 0.050% or less.

[0023] Sn: 0.010%-1.00% and Sb: 0.010%-1.00%, one or both of which is 0.11% or more in total Sn and Sb are elements that have the effect of improving the strength of steel sheet by solid solution strengthening and the effect of decreasing the pickling speed. Therefore, one or both of Sn and Sb are contained. However, if the content of each is less than 0.010%, or if the total content is less than 0.11%, the effect of improving the strength of the steel sheet is not sufficiently obtained. Therefore, when they are contained, the Sn content and the Sb content are each set to 0.010% or more, and the total content is set to 0.11% or more. The Sn content and the Sb content are preferably 0.04% or more, or 0.07% or more, respectively. The total content is preferably 0.14% or more. On the other hand, if the Sn content or Sb content exceeds 1.00%, the deformability of the steel sheet decreases. Therefore, the Sn content and the Sb content are each set to 1.00% or less. The Sn content and the Sb content are preferably set to 0.80% or less. The upper limit of the total content is 2.00%, which is the sum of the upper limits of the Sn content and the Sb content.

[0024] N: 0.0050% or less N is an element that causes strain aging. When strain aging occurs, the workability of the steel sheet is impaired. Therefore, it is better to have a low N content, but N may be mixed in as an impurity, and excessive reduction of the N content requires a long processing time at the steelmaking stage, which increases the steelmaking cost. Therefore, taking into consideration the balance between cost and properties, the N content is set to 0.0050% or less. The N content is preferably 0.035% or less. From the viewpoint of steelmaking cost, the N content may be set to 0.0005% or more or 0.0010% or more.

[0025] Cr: 0.010~1.00% Cr is an element that generates inclusions containing O and contributes to improving the resistance to chipping. If the Cr content is less than 0.010%, sufficient effects cannot be obtained. Therefore, the Cr content is set to 0.010% or more. The Cr content is preferably 0.03% or more. On the other hand, if the Cr content exceeds 1.00%, the workability deteriorates and the black spot resistance decreases. Therefore, the Cr content is set to 1.00% or less. The Cr content is preferably 0.50% or less, more preferably 0.30% or less, and further preferably 0.08% or less.

[0026] ([Sn]+[Sb]) / [P]:2.0~11.5 In the steel sheet according to this embodiment, the chemical composition includes Sn, Sb, and P contents each within the above ranges, and when the Sn content is [Sn], the Sb content is [Sb], and the P content is [P], in mass%, the ratio ([Sn]+[Sb]) / [P] is controlled to satisfy 2.0 to 11.5. In the enamel pretreatment process, which consists of degreasing, pickling, and Ni treatment, Cu is precipitated on the surface of the steel sheet by pickling, and Ni is precipitated using the Cu as precipitation nuclei in the Ni treatment, forming a local cell due to the potential difference between the steel sheet base and the Ni, which creates an anchor effect in which the enamel layer formed by firing after applying the glaze penetrates into the parent phase, improving enamel adhesion. Enamel adhesion is affected by the pickling weight loss on the surface of the steel sheet during pickling, so control of the pickling weight loss is important. Sn and Sb have the effect of reducing pickling weight loss, while P has the effect of increasing pickling weight loss. In order to improve adhesion while taking into account their mutual influence, the Sn content, Sb content, and P content are adjusted so that the ratio of the total content of Sn and Sb to the P content, ([Sn] + [Sb]) / [P], is 2.0 or more and 11.5 or less. If ([Sn]+[Sb]) / [P] is less than 2.0, the amount of Cu immersion plated onto the steel sheet surface is small due to the small pickling weight loss during pretreatment for enamel, and the amount of Ni precipitated using the Cu as a nucleus during Ni treatment is also small. As a result, the anchor effect due to the enamel layer biting into the base steel during firing cannot be obtained. ([Sn]+[Sb]) / [P] is preferably 2.3 or more, more preferably 2.5 or more, even more preferably 3.0 or more, and even more preferably 3.5 or more. On the other hand, if ([Sn]+[Sb]) / [P] is more than 11.5, the pickling weight loss increases and the surface of the steel sheet is covered with smut containing Cu. As a result, the anchor effect due to the enamel layer biting into the base steel during firing cannot be obtained. ([Sn]+[Sb]) / [P] is preferably 11.0 or less, more preferably 10.0 or less. FIG. 1 is a diagram showing the relationship between adhesion (enamel adhesion) and ([Sn]+[Sb]) / [P].

[0027] Total of one or more of B, Ni, Nb, As, Ti, Se, Ta, W, Mo, La, Ce, Ca, Mg: 0.100% or less B, Ni, Nb, As, Ti, Se, Ta, W, Mo, La, Ce, Ca and Mg are elements that react with oxide-forming elements. If the total content of these elements exceeds 0.100%, it becomes difficult to control the oxide to a state favorable for enamel properties. Furthermore, when these elements act as deoxidizing elements, they may affect the value of free oxygen, making it difficult to adjust the free oxygen. Therefore, it is preferable to set the upper limit of each element to a range that does not affect the value of free oxygen at the casting stage. Therefore, the content of these elements is set to 0.100% or less, and the total content is preferably 0.050% or less, and more preferably 0.010% or less. These elements are not necessarily contained, and may be mixed in as impurities, but are permissible as long as they are within the upper limits mentioned above. Generally, these elements are rarely mixed in alone, and are often mixed in combinations of two or more elements, such as Mo and Ni.

[0028] Remainder: Fe and impurities The chemical composition of the steel sheet according to the present embodiment contains the above, with the balance being Fe and impurities. The impurities refer to elements that are mixed in from raw materials such as ore and scrap, or the manufacturing environment, during industrial production of the base steel sheet, and are allowed to be contained in amounts that do not adversely affect the function of the steel sheet according to the present embodiment.

[0029] <Metal structure> The microstructure (metal structure) of the steel sheet according to this embodiment is mainly composed of ferrite (e.g., 98% or more) like conventional steel sheets for enamel, and therefore solid solution strengthening is effective for improving the tensile strength. When the steel sheet according to the present embodiment is processed into an enamel product, the heat treatment (enameling treatment) causes grain growth of ferrite, increasing the crystal grain size, and decreasing the yield stress and tensile strength. Therefore, using solid solution strengthening with P is effective in ensuring the tensile strength of the steel sheet after the heat treatment (enameling treatment). On the other hand, if P is contained, the pickling weight loss during enamel pretreatment becomes excessive, making it difficult to obtain excellent enamel properties (resistance to chipping, adhesion, appearance). Therefore, as described above, Sn and Sb are contained as elements that reduce the pickling weight loss, and the pickling weight loss is adjusted.

[0030] <Mechanical properties> The steel sheet according to the present embodiment has a tensile strength of 340 MPa or more in order to obtain a tensile strength of 310 MPa or more in the enameled steel sheet (enameled product). If the tensile strength after enameling is 310 MPa or more, it contributes to weight reduction of parts in enameled products. There is no upper limit to the tensile strength, but from the viewpoint of processability, the tensile strength may be 600 MPa or less. In this embodiment, the tensile strength is obtained by a tensile test performed in accordance with JIS Z2241:2011. The steel sheet according to the present embodiment further preferably has a yield stress (YS) or 0.2% proof stress (0.2% PS) of 240 MPa or more, which suppresses plastic deformation when used as an enamel product, making it possible to make the steel sheet thinner.

[0031] By performing cold rolling, voids are generated at the interface between the oxide and the base material, and the nail chip resistance after the enamel treatment is improved. Therefore, the steel sheet according to the present embodiment is preferably a cold-rolled steel sheet. In addition, the steel sheet according to this embodiment has excellent enameling properties, and is therefore preferably used as a steel sheet for enameling, which is a material for enamel products.

[0032] [Enamel products] The enamel product according to the present embodiment includes a steel plate having the above-mentioned chemical composition. For example, the enamel product is obtained by subjecting the steel plate according to the present embodiment to an enamel treatment and processing it as necessary.

[0033] [Steel plate manufacturing method] The steel sheet according to this embodiment can be effective as long as it has the above-mentioned characteristics regardless of the manufacturing method, but a manufacturing method including the following steps is preferable because it can be stably manufactured. (I) A steelmaking and casting process for producing steel billets having the above-mentioned chemical composition by melting, refining and casting; (II) a hot rolling step in which the obtained steel slab is heated, hot rolled, and coiled to obtain a steel sheet (hot-rolled steel sheet); (III) a cold rolling process in which the steel sheet after the hot rolling process is cold rolled as necessary to obtain a steel sheet (cold-rolled steel sheet); (IV) An annealing process in which the steel sheet after the cold rolling process (cold-rolled steel sheet) is annealed as necessary; (V) A temper rolling process in which temper rolling is performed on the steel sheet after the annealing process as necessary. Preferred conditions for each step will be described below. For conditions and steps not described, publicly known conditions can be applied.

[0034] <Steelmaking and casting process> In the steelmaking and casting process, steel billets having the above-mentioned chemical composition are produced by melting, refining, and casting. There are no particular restrictions on the conditions. For example, the steel billets can be those produced by continuous casting slabs or thin slab casters, and are suitable for processes such as continuous casting-direct rolling (CC-DR), in which hot rolling is performed immediately after casting. In addition, a process in which thin steel plates are directly produced by strip casters and in-line rolling machines can also be applied.

[0035] <Hot rolling process> In the hot rolling process, the obtained steel slab is heated, hot rolled, and coiled to form a steel sheet (hot-rolled steel sheet). When the steel slab is heated prior to hot rolling, the heating temperature is preferably 1150 to 1250° C. If the heating temperature exceeds 1250° C., a large amount of primary scale is generated, resulting in a decrease in yield. On the other hand, if the heating temperature is less than 1150° C., the rolling load increases due to the temperature drop during rolling. In the hot rolling process, oxides containing Fe and Mn generated in the steelmaking and casting processes are elongated by hot rolling. By setting the cumulative reduction in the finish rolling of hot rolling to 30% or more, it is possible to sufficiently elongate the oxides containing Fe and Mn in the steel. If the cumulative reduction exceeds 90%, the oxides in the steel may be too elongated, making it impossible to obtain good nail chip resistance. Therefore, it is preferable to set the cumulative reduction in the finish rolling to 30 to 90%. In addition, the finishing temperature of the hot rolling (finish rolling completion temperature) is preferably 900 to 950°C. If the finishing temperature of the hot rolling is 900°C, the rolling is performed below the transformation point, and the mechanical properties such as ductility as a product deteriorate, and at the same time, the strength change of the steel sheet increases, so that the rolling tends to become unstable. In addition, if the finishing temperature is 900°C, the microstructure of the hot-rolled steel sheet becomes a mixed grain containing coarse grains, and there is a concern that ridging will occur after processing in the cold-rolled annealed sheet using this hot-rolled steel sheet. Therefore, the finishing temperature is preferably 900°C or higher. On the other hand, if the finishing temperature exceeds 950°C, the crystal grain size becomes coarse, making it difficult to ensure the desired strength. Therefore, the finishing temperature is preferably 950°C or lower. In addition, since the steel sheet according to this embodiment utilizes solid solution strengthening of P, Sb, and Sn, it is preferable to cool the steel sheet from the end of hot rolling to the start of coiling at an average cooling rate of 15° C. / sec or more. If the average cooling rate before coiling is less than 15° C. / sec, a sufficient amount of solid solution cannot be obtained, resulting in a decrease in strength. The coiling temperature is preferably 500 to 600°C. If the coiling temperature is less than 500°C, it becomes difficult to ensure that the microstructure after cold rolling and continuous annealing has the ductility and r-value required for processing. On the other hand, if the coiling temperature exceeds 600°C, a large amount of Fe·P compounds precipitates, making it difficult to ensure the desired steel sheet strength.

[0036] <Cold rolling process> When the steel sheet according to the present embodiment is a cold-rolled steel sheet, the hot-rolled steel sheet is pickled as necessary and then cold-rolled. The cold rolling reduction rate (accumulated reduction rate in the cold rolling process) is important for determining the characteristics of the product, and is preferably 65 to 85%. The oxides containing Fe and Mn formed in the steelmaking and casting processes are elongated according to the accumulated reduction rate in the hot rolling process. After that, they are further elongated in the cold rolling process, but cold rolling is a process at a maximum of about 150°C, and the above oxides are hard and therefore difficult to elongate. Therefore, in order to elongate moderately, it is preferable to perform cold rolling at a cold rolling reduction rate of 65% or more. At this time, voids are generated at both ends of the oxide in the rolling direction. The presence of these voids is effective for the nail chip resistance but is disadvantageous for ductility. Therefore, the presence of more voids than necessary causes a decrease in ductility and therefore a decrease in workability. For this reason, the cold rolling rate is set to 90% or less.

[0037] <Annealing process> The cold-rolled steel sheet may be annealed. When annealing is performed, the annealing temperature is preferably 650 to 850°C. If the annealing temperature is less than 650°C, recovery and recrystallization are incomplete, and there is a concern that the mechanical properties may change significantly when the annealing temperature varies. In addition, as the strength increases, the ductility decreases, resulting in poor workability. On the other hand, the annealing temperature may be less than 650°C in order to impart characteristics to mechanical properties such as strength. In addition, if the annealing temperature exceeds 850°C, the mechanical properties such as ductility are improved, which is preferable, but the voids generated in the cold rolling process tend to disappear due to diffusion, and the resistance to chipping deteriorates. For this reason, the annealing temperature is preferably 850°C or less. In terms of productivity, the annealing is preferably continuous annealing.

[0038] <Temper rolling process> After the annealing process, temper rolling may be performed mainly for the purpose of shape control. In temper rolling, the amount of strain introduced into the steel sheet changes depending on the temper rolling reduction ratio while controlling the shape. In this case, if the temper rolling reduction ratio becomes large, that is, if the amount of strain introduced into the steel sheet becomes large, it will promote abnormal grain growth during the enamel treatment. For this reason, the upper limit of the temper rolling reduction ratio is the reduction ratio at which shape control is possible, and it is not desirable to impart more strain than necessary. From the viewpoint of shape control, the reduction ratio of temper rolling is preferably 1.5% or less.

[0039] [Manufacturing methods for enamel products] Moreover, the enamel product according to this embodiment is obtained by processing the steel sheet according to this embodiment (for example, the hot-rolled steel sheet after the hot rolling process described above, or the cold-rolled steel sheet after the annealing process described above, or the cold-rolled steel sheet after the temper rolling described above) into a predetermined shape, assembling it into a product shape by welding or the like, and subjecting it to an enameling process (firing process). In the enameling process, for example, the steel sheet coated with the glaze may be heated to a predetermined temperature and held for a predetermined time to allow the glassy part of the glaze to adhere to the steel sheet. The preferable firing conditions for the steel sheet according to this embodiment are, for example, a firing temperature of 700 to 900°C and a firing time of 1.5 to 20 minutes (in the furnace). Firing may be repeated several times for the second coating and repair. By carrying out the firing process under such conditions, the oxides and iron carbides can suppress grain growth during the enameling process, thereby suppressing a decrease in strength. The firing conditions shown here are merely examples and do not limit the conditions for the enameling process of the steel sheet according to this embodiment. EXAMPLES

[0040] Steels having the chemical compositions shown in Tables 1A and 1B (the balance being Fe and impurities) were melted in a converter and then formed into slabs by continuous casting. These slabs were heated to 1200°C, and then hot-rolled including finish rolling under the conditions shown in Table 2, cooled to the coiling temperature shown in Table 2 at the average cooling rate shown in Table 2, and coiled to obtain hot-rolled steel sheets. The hot-rolled steel sheets were then pickled and cold-rolled at a cumulative rolling reduction of 80% to obtain cold-rolled steel sheets. Thereafter, the annealing temperature was set to 750° C. and continuous annealing was performed. After continuous annealing, the steel sheets were subjected to temper rolling at a rolling reduction rate of 0.5% to obtain steel sheets (cold-rolled steel sheets) with a thickness of 0.7 mm.

[0041] The tensile properties of the obtained steel sheets were evaluated in the following manner.

[0042] [Tensile properties of steel plate] In accordance with JIS Z2241:2011, No. 5 test pieces were taken in the rolling direction and subjected to tensile tests to determine the tensile strength (TS) and yield stress (YS) or 0.2% proof stress (0.2%PS). If the tensile strength was 340 MPa or more, it was determined to be high strength.

[0043] In addition, in order to evaluate the properties of the obtained steel sheets after enameling (corresponding to the properties of enamel products), the tensile properties and enamel properties (nail chipping resistance, enamel adhesion, and appearance after enamel treatment) were evaluated as follows.

[0044] [Tensile properties after enameling] The obtained steel sheets were subjected to a heat treatment simulating enamel at a furnace temperature of 860°C for 5 minutes. For this heat-treated steel plate, No. 5 test pieces were taken in the rolling direction and subjected to a tensile test in accordance with JIS Z2241:2011 to determine the tensile strength (TS) and the yield stress (YS) or 0.2% proof stress (0.2%PS). If the tensile strength was 310 MPa or more, it was determined to be high strength.

[0045] [Resistant to nail chips] A sample measuring 150 mm x 100 mm was taken from the obtained steel plate, and as a pretreatment, the sample was degreased with an alkali, then immersed in a 15 g / L nickel sulfate solution at 70°C for 7 minutes, and then neutralized. Thereafter, 100 μm of Nippon Ferro 102# glaze was applied to both sides, and the piece was fired at 860°C for 5 minutes in an atmosphere with a dew point of 35°C. The baked samples were heated at 150°C for 20 hours, and the occurrence of nail chipping was visually observed and evaluated. The evaluation criteria were as follows: S: particularly excellent, A: excellent, B: normal, C: problematic, with C being a failure. S: The number of chipped nails is 5 or less per face. A: The number of nails that break off is 6 to 10 per face. B: The number of nails that break off is 11 to 20 per face. C: More than 21 nails / face

[0046] [Enamel adhesion] A sample measuring 150 mm x 100 mm was taken from the obtained steel plate, and as a pretreatment, the sample was degreased with an alkali, then immersed in a 10% sulfuric acid solution at 70°C for 10 minutes, and then immersed in a 15 g / L nickel sulfate solution at 70°C for 7 minutes, and then neutralized. Thereafter, 100 μm of Nippon Ferro 102# glaze was applied to both sides, and the piece was fired at 860°C for 5 minutes in an atmosphere with a dew point of 35°C. After firing, a 2 kg ball-headed weight was dropped from a height of 1 m onto the fired sample, and the degree of enamel peeling in the deformed areas was measured using 169 palpable needles, and evaluated in terms of the area percentage of the unpeeled areas. The evaluation criteria were as follows: A: excellent, B: normal, C: questionable, with C being a failure. A: The area ratio of unpeeled parts is 90% or more B: The area ratio of unpeeled parts is 85% or more and less than 90% C: The area ratio of unpeeled parts is less than 85%

[0047] [exterior] A sample of 150 mm x 100 mm size was taken from the steel plate, and as a pretreatment, the sample was degreased with an alkali, then immersed in a 15 g / L nickel sulfate solution at 70°C for 7 minutes, and then neutralized. Thereafter, 100 μm of Nippon Ferro 102# glaze was applied to both sides, and the piece was fired at 860°C for 5 minutes in an atmosphere with a dew point of 35°C. After firing, the appearance of the samples was visually observed and the condition of bubbles and black spots was evaluated. If even one bubble or black spot was found, it was judged as having bubble or black spot presence, and if no bubble or black spot was found, it was judged as having no problem.

[0048] [Table 1A]

[0049] [Table 1B]

[0050] [Table 2]

[0051] [Table 3A]

[0052] [Table 3B]

[0053] As can be seen from Tables 1A to 3B, in the invention examples C1 to C24, the chemical compositions were within the preferred range, the tensile strength was 340 MPa or more, and the nail chip resistance, adhesion, and appearance were excellent. In contrast, the comparative examples c1 to c23 and c27 had chemical compositions outside the range of the present invention, and either had a tensile strength of less than 340 MPa or did not achieve the targets for one or more of the resistance to chipping, adhesion and appearance. In addition, in comparative examples c24 to c26, although the chemical compositions were within the range of the present invention, the manufacturing conditions were outside the preferred conditions, and the tensile strength was less than 340 MPa. [Industrial Applicability]

[0054] According to the present invention, it is possible to provide a steel sheet that has high strength and excellent enamel properties (nail chipping resistance, adhesion, and appearance) after enameling. The tensile strength of this steel sheet after enameling is higher than that of conventional steel sheets for enameling. Therefore, it is suitable as a steel sheet for enameling, which is the base material for enamel products applied in the fields of kitchen utensils, building materials, energy, etc., and contributes to weight reduction of the products.

Claims

1. In mass percent, C: 0.0050% or less, Si: 0.050% or less, Mn: 0.007 to 1.00%, P: 0.020-0.200%, S: 0.005-0.050%, Al: 0.010% or less, O: 0.0100-0.1000%, Cu: 0.010-0.060%, N: 0.0050% or less, Cr: 0.010-1.00%, Sn: 0.010-1.00% and Sb: 0.010-1.00%, the total of one or both of which is 0.11% or more; One or more selected from the group consisting of B, Ni, Nb, As, Ti, Mo, Se, Ta, W, La, Ce, Ca, and Mg: 0 to 0.100% in total, and The balance: Fe and impurities, having a chemical composition consisting of When the Sn content, Sb content, and P content, in mass%, are [Sn], [Sb], and [P], respectively, the following formula (1) is satisfied: The tensile strength obtained by a tensile test performed in accordance with JIS Z2241:2011 is 340 MPa or more. A steel plate characterized by: 2.0≦([Sn]+[Sb]) / [P]≦11.5 (1)

2. The [Sn], the [Sb], and the [P] satisfy the following formula (2):

2. The steel sheet according to claim 1 , 2.3≦([Sn]+[Sb]) / [P]≦11.0 (2)

3. The steel plate according to claim 1, characterized in that the yield stress or 0.2% proof stress obtained in the tensile test is 240 MPa or more.

4. The steel plate according to claim 2, characterized in that the yield stress or 0.2% proof stress obtained in the tensile test is 240 MPa or more.

5. The steel sheet according to any one of claims 1 to 4, characterized in that it is a cold-rolled steel sheet.

6. The steel sheet according to any one of claims 1 to 4, which is a steel sheet for enamel.

7. The steel sheet according to claim 5, which is a steel sheet for enamel.

8. 3. An enamel product comprising a steel plate having the chemical composition according to claim 1 or 2, and having a tensile strength of 310 MPa or more in a tensile test performed in accordance with JIS Z2241:2011.

Citation Information

Patent Citations

  • High tensile cold rolled steel plate for enamel

    JP1983031063A

  • Hot rolled steel sheet for enamel having high strength after baking and superior fish scale resistance and manufacture thereof

    JP1986117246A

  • Cold rolled steel sheet for porcelain enameling, excellent in deep drawability, and its production

    JP1999006030A

  • Cold rolled steel sheet for porcelain enameling, hardly causing strength reduction after firing

    JP2000063985A

  • Method for manufacturing ultra-low carbon steel slabs, strips, or sheets

    JP2013500391A